Penegakan Hukum, Sanksi dan Kendala Dari Pelanggaran Peraturan Daerah Nomor 13 Tahun 2012 Tentang Pengelolaan Sampah di Kabupaten Kendal - Qikhan Maulidya; Dyah Listyarini; Wenny Megawati (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Waste management is still an unresolved problem to this day. This research aims to examine problems in waste management in Kendal Regency. This research is normative legal research with a statutory approach. Data was collected using literature studies and analyzed qualitatively. Kendal Regency has several laws and regulations related to waste management, especially Regional Regulation Number 13 of 2012 concerning Waste Management and several other laws and regulations. Law enforcement in waste management refers to three legal systems which are a combination of structural, material and cultural components. Apart from that, related to law enforcement in waste management, it can be studied from 2 sides, namely preventive and repressive law enforcement. Even though a strong legal basis has been provided by regional regulations, the implementation of sanctions still faces problems. The main obstacles are low public awareness, limited resources, and technical problems in waste management infrastructure. Sanctions applied for violations of regulations include verbal warnings, written warnings and fines. Sanctions have not been able to provide significant deterrence, according to the evaluation. Therefore, this research provides suggestions for improving the law enforcement system, increasing public awareness, and overcoming technical problems so that Regional Regulation Number 13 of 2012 in Kendal Regency can be better implemented in terms of sustainable waste management. Effective law enforcement can help create a clean, healthy and sustainable environment while ensuring that each party is responsible for waste management.